Analisis Pengaruh Pembiayan Perbankan Syariah terhadap UMKM untuk Pengentasan Kemiskinan di Indonesia - Fadila, Dinda; Karimi, Syafruddin; Kamarni, Neng (SAFE-Network, 2025)
This study aims to analyze the impact of Islamic banking financing on the development of MSMEs and poverty alleviation in Indonesia. The method used is a literature review by analyzing secondary data from OJK, BPS, and relevant academic literature. The results show that Islamic banking financing significantly supports MSME growth and positively impacts poverty reduction, especially during the post-pandemic period. Policy implications emphasize the need to strengthen the role of Islamic financial institutions in supporting MSMEs as a sustainable poverty alleviation strategy. These findings contribute to the Islamic economics literature and inclusive development policy in Indonesia.